The specific features of cerebrovascular disease in systemic lupus erythematosus - D L Faizulina; V V Shprakh; Alexey Nikolayevich Kalyagin (Современная ревматология, 2012)
The paper discusses the problems of cerebrovascular disease in patients with systemic lupus erythematosus. It proposes a procedure for managing this category of patients.